دور الانثـروبولوجــيا التطـبيقيـة فــي حــل مشاكل التـنمـية - د. علي كاظم حمزة (Thi Qar Arts Journal, 2021)
Applied anthropology is defined as that section of anthropology that is concerned with describing the changes in human relations and the efficacy of the principles that control human organization. Practically speaking, applied anthropology has been considered as that domain that provides accurate knowledge about local communities to all those who have a responsibility to make decisions about these communities.     The incorporation and employment of knowledge of people’s cultures into achieving certain goals is an old matter; the idea of applied anthropology has begun since the moment the first contact between early western communities and tribal and rural communities. However, these beginnings did not meet the process required by applied anthropology. In fact, the intellectual climate for that period of the sixteenth and eighteenth centuries was devoid of awareness of scientifically recognized methods of anthropological research and application. For such reasons, the colonial administrative, economic and social plans have failed to address the problems of early communities despite the attempts of the ruling administrations. Applied anthropology has since emerged as a great advocate of the concept of cultural relativism, recognizing the mobility of society, rejecting cultural stagnation and emphasizing the inclusion of the development planning process, which aims to enable societies to achieve general social change while, at the same time, preserving their cultural identity.Anthropologists, like other scientists, have put their knowledge at the service of solving scientific problems. They partner with scholars in other relevant disciplines and government agencies in an attempt to solve problems associated with social control, education and public welfare. In a number of civilized societies, anthropologists apply their own methods to solving inter-racial problems, problems of child rearing, personality development, questions of national character, and problems of industrial relations. Besides, the local culture may also constitute an obstacle to the development of modern economies and the inability to provide the appropriate ground for building a modern and developed society without making fundamental changes in these societal values